PELAKSANAAN PROGRAM JAMSOSTEK DITINJAU DARI PERSPEKTIF PERLINDUNGAN HUKUM TENAGA KERJA - -, Dahlia - (Wacana Hukum, 2012)
Abstract: Jamsostek program is a form of economic and social protection programs to provideprotection in the form of compensation for the loss of income in the form of cash andprotection in the form of services, care or treatment at the time of a worker hit bycertain risks. Jamsostek existence as living safeguard employment in a company isvery beneficial, and therefore as a measure to ensure the life of labor, the companywill enter the workforce in Jamsostek program managed by PT. JAMSOSTEK.Key words: Jamsostek Program, Worker Protection Law